162. CD377, a Novel Antiviral Fc-conjugate, Demonstrates Potent Viral Burden Reduction Against Influenza a (H1N1) in Mouse and Ferret Models. (31st December 2020) - Döhrmann, Simon; Almaguer, Amanda; Dedeic, Nicholas; Amundson, Karin; Shathia, Kim; Brady, Thomas P; Noncovich, Alain; Zhao, Qiping; Hough, Grayson; Borchardt, Allen; Locke, Jeffrey B; Cole, Jason; et al.
Abstract: Background: AVCs (antiviral Fc-conjugates) are novel, long-acting immunotherapeutic conjugates of potent antivirals conjugated to the Fc domain of human IgG1. CD377, an AVC development candidate for the prevention and treatment of influenza A and B, comprises multiple copies of a novel neuraminidase inhibitor conjugated to IgG1 Fc. CD377 demonstrated potent, broad-spectrum activity in vitro and in lethal mouse models. Herein, we characterize the activity of CD377 on viral lung burden in lethal mouse models and in a ferret model of influenza A (H1N1) infection. Methods: BALB/c mice were challenged intranasally with 3 x 10 2 PFU of influenza A/PR/8/1934 (H1N1) or with 3 x 10 4 PFU A/CA/07/2009 (H1N1)pdm. Ferrets were challenged sub-lethally at 1 x 10 6 PFU with influenza A/CA/07/2009 (H1N1)pdm. A single dose of CD377 was given 2 h post-challenge in the mouse (subcutaneous dose ranging from 0.1 – 3 mg/kg) or 24 h prior to challenge in the ferret (intravenous dose ranging from 0.3 – 30 mg/kg). In mice, oral oseltamivir was given at 5 mg/kg (human equivalent dose, HED) or at 50 mg/kg BID x 4 days starting at 2 h post-challenge and in ferrets at 20 mg/kg (4x HED) BID x 4 days starting at 4 h prior to infection. Viral burden was determined on day 4 (mouse) or days 2 and 4 (ferret) post-challenge by plaque assay. Results: In mice, CD377 demonstrated dose-dependent reduction in viral lung burden (1.1 logs at 0.1 mg/kg, 2.1 logs at 0.3 mg/kg, 3.1 logs at 1 mg/kg and 3.6 logs at 3 mg/kg) compared to PBS against influenza A/PR/8/1934 (H1N1) (Fig. 1A). In the same study, oseltamivir reduced viral lung burden only by 0.8 logs at both 5 mg/kg (HED) and 50 mg/kg. No significant reduction in lung burden was observed between negative controls, PBS and hIgG1 Fc. Similarly, CD377 demonstrated a dose-dependent, multi-log reduction in viral lung burden against influenza A/CA/07/2009 (H1N1)pdm (Fig. 1B). In ferrets, CD377 reduced viral load with dose dependency at days 2 (Fig. 1C) and 4 post-infection (Fig. 1D). CD377 at 3 mg/kg or higher dose was superior compared to oseltamivir at 4x HED on days 2 and 4 post-challenge. Conclusion: CD377 demonstrated superior viral load reduction compared to oseltamivir in lethal influenza A (H1N1) mouse and ferret models. These data support further development of CD377 for prevention and treatment of influenza infection. Disclosures: Simon Döhrmann, PhD, Cidara Therapeutics (Shareholder) Amanda Almaguer, Bachelors, Cidara Therapeutics, Inc. (Employee, Shareholder) Nicholas Dedeic, n/a, Cidara Therapeutics (Employee) Karin Amundson, BSc, Cidara Therapeutics (Shareholder) Thomas P. Brady, PhD Chemistry, Cidara Therapeutics (Employee) Alain Noncovich, PhD, Cidara Therapeutics (Shareholder) Grayson Hough, MS - Chemistry, Cidara Therapeutics (Employee) Allen Borchardt, PhD, Cidara Therapeutics (Employee) Jeffrey B. Locke, PhD, Cidara Therapeutics, Inc. (Employee, Shareholder) Jason Cole, PhD, Cidara Therapeutics (Shareholder) James Levin, PhD, Cidara Therapeutics (Shareholder) Les Tari, PhD, Cidara Therapeutics (Shareholder)